(untitled) (Advances in Applied Mathematics and Mechanics, 2018)
We consider the approximation of eigenvalue problems for elasticity equations with interface. This kind of problems can be efficiently discretized by using immersed finite element method (IFEM) based on Crouzeix-Raviart P1-nonconforming element. The stability and the optimal convergence of IFEM for solving eigenvalue problems with interface are proved by adopting spectral analysis methods for the classical eigenvalue problem. Numerical experiments demonstrate our theoretical results.